VATAR OF METHOD (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the secant method, an iterative numerical technique used to approximate the roots of nonlinear algebraic equations. Unlike the Newton-Raphson method, which requires the computation of derivatives, the secant method relies on drawing a secant line through two initial approximations to generate successive estimates of the root. The paper discusses the theoretical foundation of the method, its advantages and limitations, and provides a step-by-step implementation using the Python programming language. A detailed example is presented to demonstrate how the secant method can be effectively applied to find the positive root of a specific algebraic equation. Due to its simplicity and ease of implementation, the secant method remains a practical and widely used tool in numerical analysis.